Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Racial Logics, Franchising, and Video Game Genres: The Lord of the Rings - Young, Helen (Games and Culture, 2016)
This article explores the ways game adaptations engage with existing popular culture constructions of race within the framework of commercial franchises. Its focus is on games which are part of the so-called “Frodo Franchise” based on Peter Jackson’s Lord of the Rings and The Hobbit films. It considers the role played by licensing agreements, the conventions, and ludic elements of different game genres, the need for new characters and narratives to keep audiences engaged with an existing world, and the opportunity games offer for interactive exploration of a digital world, to illuminate both the challenges to and the opportunities for disrupting conventional representations of race and difference.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé

Counterfactual Communities: Strategy Games, Paratexts and the Player’s Experience of History - Apperley, Tom (Open Library of Humanities, 2018)
The genre of history strategy games is a crucial area of study because of what is at stake in the representation of controversial aspects of history in popular culture. Previous work has pointed to various affordances and constraints in the representation of history, based on the framing of the game interface, the alignment of goals with certain strategies and textual criticism of the contents of the games. In contrast, this article examines these games from the perspective of the player’s experience of play in relation to a wider gaming community. It is in these counterfactual communities that players negotiate their individual experience with their knowledge of the history that is presented in the games that they play, indicating that the relationship between digital games, players and history is highly contextual. The relevant practices of players of history strategy games are illustrated with examples from the official and unofficial communities of the Paradox Interactive games Europa Universalis II and Victoria: Empire Under the Sun. The shared paratexts demonstrate how positions are negotiated in relation to the ‘official’ version of history presented in the games. These negotiations are made tangible through the production and sharing of paratexts that remix the official history of the games to include other perspectives developed through counterfactual imaginations. These findings indicate the importance of including perspectives from gaming communities to support other forms of analysis in order to make rigorous observations about the impact of digital games on popular history.
Number: 1
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé